2021
DOI: 10.1111/ppl.13449
|View full text |Cite
|
Sign up to set email alerts
|

AlRab7 from Aeluropus lagopoides ameliorates ion toxicity in transgenic tobacco by regulating hormone signaling and reactive oxygen species homeostasis

Abstract: The plants endomembrane system of the cellular compartments with its complex membrane trafficking network facilitates transport of macromolecules. The endomembrane dynamics are essential for maintaining basic and specific cellular functions including adaptation to the extracellular environment. The plant vacuole

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In addition, ectopic overexpression of the N. tangutorum calcineurin B-like protein-interacting protein kinase 11 (NtCIPK11) gene from N. tangutorum in Arabidopsis improved seed germination and root length, as well as altered the transcription of genes encoding key enzymes involved in proline metabolism and K + transportation in transgenic plants subjected to salt stress [155,156] (Table 2). Transgenic tobacco plants ectopically expressing several novel genes from S. brachiata, such as S. brachiata stress-related protein (SbSRP), S. brachiata salt inducible-1 (SbSI-1), S. brachiata myeloblastoma15 (SbMYB15), S. brachiata dehydration-responsive element-binding 2A (SbDREB2A), and S. brachiata RNA poly III complex 5-like subunit (SbRPC5L), and Aeluropus lagopoides, such as AlRab7 (AlRabring7), displayed higher accumulations of phytohormones (e.g., indole acetic acid) and compatible solutes (e.g., proline), improved gas exchange features, reduced membrane damage, improved antioxidant capacity, lower accumulations of toxic ions, ultimately resulting in better biomass and growth performance of transgenic plants under salt stress [157][158][159][160][161][162] (Table 2). In addition, ectopic expression of L. maritima vacuolar H+-ATPase subunit E1 (LmVHA-E1) from L. maritima, Tamarix hispida dehydration-responsive element-binding (ThDREB) from T. hispida, PutNHX1 or PutAPX from P. tenuiflora, or SeNHX1 from S. europaea in Arabidopsis plants improved ROS-scavenging, as well as compartmentalization of toxic Na + into vacuoles to enhance salt tolerance of transgenic plants [150,163,164] (Table 2).…”
Section: Potential Of Halophytes As Genetic Resources For the Engineering Of Crops With Improved Salt Tolerancementioning
confidence: 99%
“…In addition, ectopic overexpression of the N. tangutorum calcineurin B-like protein-interacting protein kinase 11 (NtCIPK11) gene from N. tangutorum in Arabidopsis improved seed germination and root length, as well as altered the transcription of genes encoding key enzymes involved in proline metabolism and K + transportation in transgenic plants subjected to salt stress [155,156] (Table 2). Transgenic tobacco plants ectopically expressing several novel genes from S. brachiata, such as S. brachiata stress-related protein (SbSRP), S. brachiata salt inducible-1 (SbSI-1), S. brachiata myeloblastoma15 (SbMYB15), S. brachiata dehydration-responsive element-binding 2A (SbDREB2A), and S. brachiata RNA poly III complex 5-like subunit (SbRPC5L), and Aeluropus lagopoides, such as AlRab7 (AlRabring7), displayed higher accumulations of phytohormones (e.g., indole acetic acid) and compatible solutes (e.g., proline), improved gas exchange features, reduced membrane damage, improved antioxidant capacity, lower accumulations of toxic ions, ultimately resulting in better biomass and growth performance of transgenic plants under salt stress [157][158][159][160][161][162] (Table 2). In addition, ectopic expression of L. maritima vacuolar H+-ATPase subunit E1 (LmVHA-E1) from L. maritima, Tamarix hispida dehydration-responsive element-binding (ThDREB) from T. hispida, PutNHX1 or PutAPX from P. tenuiflora, or SeNHX1 from S. europaea in Arabidopsis plants improved ROS-scavenging, as well as compartmentalization of toxic Na + into vacuoles to enhance salt tolerance of transgenic plants [150,163,164] (Table 2).…”
Section: Potential Of Halophytes As Genetic Resources For the Engineering Of Crops With Improved Salt Tolerancementioning
confidence: 99%
“…Further molecular analysis of the genes responsible for raffinose synthesis revealed an 18-fold increase in the expression of BvRS2 in the tolerant genotype, indicating its involvement in raffinose synthesis. The overexpression of AlRab7, a vesicle trafficking gene from A. lagopoides, resulted in an increase in germination and growth and curtailment in ionic and oxidative stress in transgenics (Agarwal et al, 2021). The authors concluded that the AlRab7 transgenic tobacco mitigates ionic stress by helping in differential and selective ion transport at the vacuole, regulating hormone signaling, ROS homeostasis, stomatal development, and movement.…”
mentioning
confidence: 99%